Taking Healthcare Ethics Committees Seriously (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The essay examines the current state of Clinical Ethics Committees (CECs) in Italy, highlighting their persistent marginality, despite repeated calls from the National Bioethics Committee for stronger regulation and more substantial support. It outlines the functions of CECs, identifies key challenges, and emphasizes the critical conditions necessary for their effective operation. The essay also underscores both the symbolic and practical significance of these committees. Ultimately, it argues for a more serious commitment to supporting CECs, stressing the vital role they can play in fostering ethical reflection within healthcare institutions – an essential step toward ensuring truly respectful patient care.
Keywords: healthcare ethics committees; clinical ethics committees; clinical bioethics; ethics deliberation